Preparation, Characterization and Antibacterial Studies of New 2-(naphthalene2-yl)-2-(naphthalene-2ylamino) Acetonitrile Ligand with Some Metal Ions - Al-Amery, Mohammed H A (Al-Nahrain Journal of Science, 2018)
In the present work, the synthesized of a series of metal ions complexes of [Cr(III), Fe(III), Mn(II), Co(II), Ni(II), Cu(II), Zn(II), Cd(II) and Hg(II)] from new bidentate 2-(naphthalene-2-yl)-2-(naphthalene-2ylamino) acetonitrile ligand (L) which prepared from 2-naphthaldehyde and naphthalene-2-amine in the presence of KCN and alcoholic medium. These compounds were characterized by using several techniques FT-IR, UV-Visible spectrophotometer, magnetic susceptibility, thermal gravimetric analysis (TGA), elemental analysis, molar conductivity, 1H-NMR, as well as atomic absorption. From the spectral studies, an octahedral monomer structure was proposed for all complexes. The nature of the complexes formed in ethanolic solution has been studied following the molar ratio method and the result recorded [1:2] [M:L] ratio. Some complexes were found to be non-electrolyte and others were found to be weak electrolyte in ethanol. Biological activities of the free ligand and its metal complexes have been tested against a number of microorganisms in order to assess their antimicrobial properties.